Jejunal Intussusception Secondary to a Large Inflammatory Fibroid Polyp: A Case Report and Discussion of Differential Diagnosis - Asma Khalid Abu-Salah; Eric Brocken; Hector Mesa; Katrina Collins (Case Reports in Pathology, 2023)
Inflammatory fibroid polyp (IFP), initially considered a reactive process, is now recognized as a benign mesenchymal neoplasm of the gastrointestinal tract. We report a case of a 68-year-old woman with medically refractory Crohn disease that presented with intussusception requiring surgical intervention. The resection revealed a jejunal mass consisting of a submucosal proliferation of bland spindle cells in a fibrous stroma infiltrated by numerous eosinophils. By immunohistochemistry, the lesion was positive for vimentin and negative for desmin, smooth muscle actin (SMA), S-100, CD117, DOG1, ALK (D5F3), Melan-A, HMB-45, CD34, and STAT6. Ki-67 proliferative index was low (<1%). The mass was classified as IFP by its characteristic morphology and associated eosinophilia. IFP should be considered in the differential diagnosis of adults with intussusception or bowel obstruction. Definitive treatment typically requires surgical resection of the involved bowel segment.